Echocardiographic mitral systolic motion in left ventricular aneurysm. Issue 7 (July 1975) - Greenwald, J; Yap, J F; Franklin, M; Lichtman, A M
Abstract : An abnormal, convex systolic anterior motion of the mitral valve, somewhat similar to that seen in idiopathic hypertrophic subaortic stenosis (hypertrophic obstructive cardiomyopathy) and occasionally in atrial septal defect, was found on the echocardiogram in 8 out of 9 patients with angiographically (7 patients) and/or clinically (2 patients) diagnosed left ventricular aneurysm secondary to myocardial infarction. The only patient whose echocardiogram failed to demonstrate convex systolic anterior motion was the only patient who had an inferior wall aneurysm; the rest of the group had anterior and/or apical aneurysms. In contrast to patients with typical idiopathic hypertrophic subaortic stenosis, the convex systolic anterior motion of the mitral valve observed in our patients tended to 'peak' rather than 'plateau'. Through the basis for this abnormal septal motion in our patients is uncertain, alterations in left vantricular configuration, plus a relatively vigorously contracting posterior left ventricular wall in the presence of abnormal interventricular septal motion, are probable contributory factors. Though non specific, in the proper clinical and echocardiographic setting convex systolic anterior motion of the mitral valve may be another sign of left ventricular aneurysm.